Evaluation of Agronomic Characteristics and Grain Yield Stability of Promising Lines of Rice in Guilan Province - A. R. Tarang; S. Bakhshipour (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2016)
This study was conducted to evaluate the quantitative and qualitative characteristics and grain yield stability of 10 promising lines of rice, compared to cultivar Khazar as the checking variety, in Rasht, Roudsar and Talesh cities of Guilan province, Iran, in three years. The experiment was conducted using a randomized complete block design with three replications. Characteristics such as grain yield, plant height, tiller number, panicle length, filled grain in panicle, 1000 grain weight, length, and shape of grain, days to 50% flowering and maturity, amylase content, gel consistency and gelatinization temperature were measured. The simple and combined analyses of variance were performed on grain yield data. Simple analysis of variance revealed significant differences within the genotypes. Results of combined analysis of variance indicated that there were significant differences among the grain yield of the genotypes in different years and locations. The interaction effects of location × year and location × genotype weren't significant; however, the interactions effects of genotype × location × year were significant. Stability analysis was also performed with Lin and Binns method. According to the stability analysis, lines no. 4, 7 and 8 were characterized as stable lines because of having low coefficient of variation and mean square within location. It seems, from our data, that appropriate breeding schemes based on hybridization and selection for these traits may bring about an improvement in cooking quality of rice.